The Effect of Psychological Capital and Role Conflict on the Academic Entrepreneurial Intents of Chinese Teachers in Higher Education: A Study Based on the Theory of Planned Behavior - Liao, Kai; Liu, Ziyang; Li, Bing (Frontiers in Psychology, 2022)
Abstract: The purpose of this study is to identify the individual psychological capital and role conflict issues among teachers in higher education in China, beginning with the emergence of positive academic entrepreneurial intents, continuing through the process of academic entrepreneurship, and clarifying the impact of psychological capital and role conflict on entrepreneurial intent. Based on the theory of planned behavior, we constructed a research model from the perspective of entrepreneurial intent prior to entrepreneurial action. We established a cohort of teachers in 17 higher education institutions (N = 525) in southern China, with psychological capital and role conflict as the prior independent variables and the teachers’ academic entrepreneurial intent as the dependent variables. Using quantitative analysis, SPSS 22.0, and AMOS 23.0, we conducted reliability and validity tests, correlation analysis, and structural equation models on the collected data. We reached the following conclusions: (1) Psychological capital has a positive effect on attitudes to academic entrepreneurship, (2) Psychological capital has a positive effect on perceived behavioral control, (3) Role conflict has a negative effect on perceived behavioral control, (4) Academic entrepreneurial attitudes have a positive effect on academic entrepreneurial intent, (5) Perceived behavioral control has a positive effect on academic entrepreneurial intent, and (6) Subjective norms have a positive effect on academic entrepreneurial intent. We provide some suggestions on academic entrepreneurship for administrators of Chinese and foreign universities.